A touch mode MEMS capacitance diaphragm gauge. (December 2021) - Li, Gang; Han, Xiaodong; Sun, Wenjun; Cheng, Yongjun; Li, Detian
Abstract: This paper presents a touch mode MEMS capacitance diaphragm gauge (CDG) for differential pressure measurement. The design principle of the gauge is demonstrated, then the diaphragm deflection and capacitance sensitivity are analyzed theoretically. Experimental work was carried out using a principle prototype, which has a square pressure-sensing diaphragm with large width-to-thickness ratio. The test results are consistent with the theoretical model for pressure from 1 Pa to 1000 Pa, and the capacitance-pressure curve of the gauge is near linear in three pressure sections and a maximum sensitivity of 135 fF/Pa is achieved in low pressure range. Moreover, high pressure test results ranging from 1000 Pa to atmospheric pressure indicate that the developed touch mode gauge has wide load range and good overload protection.